« Artiste et assassin » : Jules Laforgue et la complainte criminelle - Nils Couturier (Criminocorpus)
This article explores the relationship between the poet Jules Laforgue, author in 1885 of a collection entitled Les Complaintes, and the « complainte criminelle » (a form of popular song on crime). In this perspective, we analyse the treatment that Laforgue gives in one of his chronicles to the case of Jean Baffier, a sculptor and folklorist who committed a political assassination attempt. Through this text and the way it was constructed, we try to identify Laforgue’s specific poetics, in their links to popular song.